FACTORS AFFECTING THE TEENS’ INTEREST IN LEARNING THAI MUSIC - Tiengtrong, Pramote; Phensit, Tasnai; Panapinan, Sirima (FOCUS ON ARTS : FAR, SSRU, 2024)
The research titled “Factors Affecting Teenagers’ Interest in Learning Thai Music” aimed 1) to study the factors affecting the teenagers’ interest in learning Thai music 2) to study guideline on the factors affecting learning Thai music among teenagers. on the interest in learning Thai music among teenagers The sample group in this study were: There were 377 students in grades 1 - 6 at a government school in Bangkok. In this study, the researcher conducted a quantitative study. by using a questionnaire as a tool The frequency, percentage, mean, standard deviation and descriptive analysis were assessed. It consists of factors of personal characteristics. experience environment The results showed that environmental factors influenced all aspects of attention, followed by friends and family factors.